BRAND TRUST AND PERCEIVED QUALITY AS DETERMINANTS OF SKINCARE PRODUCT PURCHASE DECISIONS : THE MEDIATING ROLE OF CONSUMER ATTITUDES - Aurelia Salsabilla Almirah; Rahmawati; Yana Ulfah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The growth of the global skincare industry demonstrates a shift in consumer behavior that increasingly relies on safety evaluations and user experience in forming long-term decisions. Current literature indicates that the relationship between product perceptions and consumer loyalty remains unclear due to limitations in uncovering the underlying psychological mechanisms (Nguyen et al., 2022; Wang et al., 2023). This study aims to analyze the influence of product safety perceptions and user experience on consumer loyalty, with consumer satisfaction as the mediator. A quantitative explanatory approach was used, involving 180 respondents who used Skintific skincare products in Samarinda City, and analyzed using PLS-SEM (Hair et al., 2024). The results showed that product safety perceptions and user experience have a positive and significant effect on consumer satisfaction and loyalty. Consumer satisfaction was also shown to significantly mediate this relationship. These findings confirm that loyalty is formed through an internal evaluation mechanism that integrates cognitive and affective aspects. This study contributes by strengthening the role of satisfaction as a primary causal mechanism in explaining loyalty formation for high-risk products such as skincare.